Quoi, t’as pas Facebook?: evolving French negation in social media - Hadshi, Catherine (Lingua Frankly, 2016)
Social media provides its users with a myriad of benefits: easy event planning, communication with old friends, instant messaging, and, of course, a convenient medium by which to share all of the mundane vicissitudes of modern life. Yet within this innocent sea of friends’ photographs and enemies’ status updates, a linguistic revolution is constantly under way. Every living language, naturally, is evolving. But in French, and in social media, that evolution becomes identifiable, perhaps even traceable. By focusing on one element in the language of social media—that ubiquitous ne...pas we all encountered in Elementary French—linguistic researchers can uncover a very specific shift in usage within French’s overall grammatical system.